The best versus the rest: the global productivity slowdown, divergence across firms and the role of public policy - Andrews, Dan; Criscuolo, Chiara; Gal, Peter N. (Paris, 2016)
"In this paper, we aim to bring the debate on the global productivity slowdown – which has largely been conducted from a macroeconomic perspective – to a more micro-level. We show that a particularly striking feature of the productivity slowdown is not so much a lower productivity growth at the global frontier, but rather rising labour productivity at the global frontier coupled with an increasing labour productivity divergence between the global frontier and laggard (non-frontier) firms. This productivity divergence remains after controlling for differences in capital deepening and mark-up behaviour, suggesting that divergence in measured multi-factor productivity (MFP) may in fact reflect technological divergence in a broad sense. This divergence could plausibly reflect the potential for structural changes in the global economy – namely digitalisation, globalisation and the rising importance of tacit knowledge – to fuel rapid productivity gains at the global frontier. Yet, aggregate MFP performance was significantly weaker in industries where MFP divergence was more pronounced, suggesting that the divergence observed is not solely driven by frontier firms pushing the boundary outward. We contend that increasing MFP divergence – and the global productivity slowdown more generally – could reflect a slowdown in the diffusion process. This could be a reflection of increasing costs for laggard firms of moving from an economy based on production to one based on ideas. But it could also be symptomatic of rising entry barriers and a decline in the contestability of markets. We find the rise in MFP divergence to be much more extreme in sectors where pro-competitive product market reforms were least extensive, suggesting that policy weaknesses may be stifling diffusion in OECD economies."